Forest Influences - Krishnaswamy, V. S.; Dabral, S. N.; Nath, Prem (Indian Forester, 1957)
A study of soil temperatures and humidity was started in the Demonstration area of New Forest, F.R.I. in May I953 with a view to studying the differences in temperatures and humidity due to afforestation as compared to those in open. The interim results drawn from the data collected so far are given under "Conc1usion" at the end.